The art of baring it all: a reading of Judith Teixeira’s “Satânia” - Pazos Alonso, C (Universidade de São Paulo, 2023)
This article considers Judith Teixeira’s focus on heterosexual relationships in “Satânia.” In the light of an emerging military dictatorship and backlash after Nua and De mim, the writer seeks to uncover the double standards that required women to repress their carnal desires outside marriage. The article alludes to the scandal caused by Maria Adelaide Coelho da Cunha’s affair with her young chauffeur, publicly played out in the press, which may have sparked Teixeira’s tale of forbidden lust. Taking its cue from Saint-Point’s Manifeste futuriste de la luxure (1912), the demise of the protagonist, Maria Margarida, becomes a barely veiled criticism of social prohibitions around female sexuality.